Development of a Comorbidity-Based Nomogram to Predict Survival After Salvage Reirradiation of Locally Recurrent Nasopharyngeal Carcinoma in the Intensity-Modulated Radiotherapy Era - Huang, Run-Da; Sun, Zhuang; Wang, Xiao-Hui; Tian, Yun-Ming; Peng, Ying-Lin; Wang, Jing-Yun; Xiao, Wei-Wei; Chen, Chun-Yan; Deng, Xiao-Wu; Han, Fei (Frontiers in Oncology, 2021)
Purpose: To assess the impact of comorbidity on treatment outcomes in patients with locally recurrent nasopharyngeal carcinoma (lrNPC) using intensity-modulated radiotherapy (IMRT) and to develop a nomogram that combines prognostic factors to predict clinical outcome and guide individual treatment. Methods: This was a retrospective analysis of patients with lrNPC who were reirradiated with IMRT between 2003 and 2014. Comorbidity was evaluated by Adult Comorbidity Evaluation-27 grading (ACE-27). The significant prognostic factors (P < 0.05) by multivariate analysis using the Cox regression model were adopted into the nomogram model. Harrell concordance index (C-index) calibration curves were applied to assess this model. Results: Between 2003 and 2014, 466 lrNPC patients treated in our institution were enrolled. Significant comorbidity (moderate or severe grade) was present in 17.1% of patients by ACE-27. Patients with no or mild comorbidity had a 5-year overall survival (OS) rate of 36.2% versus 20.0% among those with comorbidity of moderate or severe grade (P < 0.0001). The chemotherapy used was not significantly different in patients with lrNPC (P > 0.05). For the rT3-4 patients, the 5-year OS rate in the chemotherapy + radiation therapy (RT) group was 30.0% versus 16.7% for RT only (P = 0.005). The rT3-4 patients with no or mild comorbidity were associated with a higher 5-year OS rate in the chemotherapy + RT group than in the RT only group (32.1% and 17.1%, respectively; P=0.003). However, for the rT3-4 patients with a comorbidity (moderate or severe grade), the 5-year OS rate in the chemotherapy + RT group vs. RT alone was not significantly different (15.7% vs 15.0%, respectively; p > 0.05). Eight independent prognostic factors identified from multivariable analysis were fitted into a nomogram, including comorbidity. The C-index of the nomogram was 0.715. The AUCs for the prediction of 1-, 3-, and 5-year overall survival were 0.770, 0.764 and 0.780, respectively. Conclusion: Comorbidity is among eight important prognostic factors for patients undergoing reirradiation. We developed a nomogram for lrNPC patients to predict the probability of death after reirradiation and guide individualized management.